SISTEM PENGAMAN KENDARAAN LISTRIK DENGAN DETEKSI WAJAH BERBASIS INTERNET OF THINGS: ELECTRIC VEHICLE SECURITY SYSTEM WITH FACE DETECTION BASED ON THE INTERNET OF THINGS - Ahmad Arya Marzuki; Esculenta, Mira; Eko, Riswan (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
The development of motor vehicle users in Indonesia continues to increase. This also triggers the occurrence of cases of motor vehicle theft. One of the causes of theft is a security system that is lacking. To overcome this problem, this research created an Internet of Things-based motor vehicle safety device. The purpose of this research is to maintain the safety of motorized vehicles from a distance. The method used is an experiment by adjusting several camera distances and PIR sensors on motorized vehicles. The resulting data will be stored and processed using Minitab software with the One Way Annova technique. The results showed that the fastest response time from the camera distance was 45cm with a time of 1.483 seconds and the longest response time from the camera distance was 20cm with a time of 4.976 seconds, the fastest response time from a PIR sensor distance was 40 cm with a time of 7.971 seconds and the longest response time from a distance PIR sensor is 20 cm with a time of 8.013 seconds.